P002 Endoscopic Characteristics and Prognosis of Pouchitis Involving the Pouch Inlet in Patients With Inflammatory Bowel Disease. (December 2019) - Akiyama, Shintaro; Ollech, Jacob; Rai, Victoria; Glick, Laura; Singer, Jorie; Karpin, Jordan; Rodriguez, Tina; Yi, Yangtian; Shaffer, Seth; Russell D, Cohen; Hurst, Roger; Hyman, Neil; et al.
Abstract : BACKGROUND: In patients with inflammatory bowel disease (IBD), surgical intervention is sometimes required due to medically refractory colitis or the development of neoplasia, and restorative proctocolectomy with ileal pouch-anal anastomosis (IPAA) is the most common procedure for those with colitis. However, pouchitis can develop in up to 80% of patients after the surgery and significantly impairs quality of life. Despite the high prevalence of pouchitis, endoscopic phenotypes have not been clarified. This study assessed the frequency of and risk factors for inflammation involving the pouch inlet. METHODS: This is a retrospective single-center study of IBD patients treated by total proctocolectomy with IPAA and who subsequently underwent pouchoscopies at the University of Chicago between January 2007 and September 2019. We reviewed the endoscopic findings in different anatomic areas of the pouch: the pre-pouch ileum, inlet, "tip of the J", proximal and distal pouch, anastomosis, rectal cuff, anal canal, and perianal area. This analysis evaluated all available pouchoscopies and included any patient who had inlet inflammation noted at least once. Demographic and clinical data were also assessed. Log-rank test was used for a univariate analysis to assess factors contributing to pouch excision. Cox proportional hazard regression analysis was performed as a multivariate analysis including univariate variables with a p -value < 0.10. RESULTS: We reviewed 1, 081 pouchoscopies from 426 IBD patients who underwent proctocolectomy with IPAA and identified 188 patients (44%) with pouchitis involving the inlet. Of these patients, 62% were men, 89% were Caucasian, mean age at diagnosis (SD) was 24 ± 11 years, and mean BMI 26 ± 5. The included patients had pre-pouch diagnoses of ulcerative colitis (165; 89%), indeterminate colitis (14; 7.5%), and Crohn's disease (7; 3.8%) as the diagnosis before surgery. Twenty-five percent (47/188) had inlet stenosis and 33% (62/188) had pouch-anal anastomotic stenosis. Compared with the cuff, the rate of ulcerations was higher in the pre-pouch ileum and inlet (27.1% vs 42% and 66%, respectively). After a mean of 12 years of follow-up, the overall prevalence of pouch excision was 14% (25/188). Multivariate analysis identified that inlet stenosis significantly predicted pouch excision (HR = 2.92; 95% CI = 1.24-6.86; p = 0.014), whereas anastomotic stenosis was not a significant predictor (HR = 1.48; 0.64-3.42; p = 0.36). CONCLUSION(S): Inlet inflammation and stenosis is present in a significant number of IBD patients with pouchitis, and stenosis in particular is associated with pouch excision. There is a pressing need to understand the causes and develop treatments of this complication.